Beriberi Induced Cardiomyopathy Requiring Salvage Venoarterial Extracorporeal Membrane Oxygenation. (5th December 2016) - Shah, Aditya; Patel, Samir; Kothari, Sorabh; Denk, Jennifer
Abstract : Beriberi refers to a constellation of symptoms caused primarily by thiamine (vitamin B1) deficiency. An acute and fulminant presentation of this rare condition has been described in the literature as "Shoshin" beriberi which is characterized by catastrophic cardiovascular collapse. Early recognition and treatment lead to dramatic improvements of symptoms. We present a case of thiamine deficiency-induced acute heart failure in a malnourished patient leading to cardiac arrest necessitating VA-ECMO (venoarterial extracorporeal membrane oxygenation) with improvement in heart function secondary to thiamine administration.